2021
DOI: 10.1002/pssr.202100033
|View full text |Cite
|
Sign up to set email alerts
|

Ferroelectric La‐Doped ZrO2/HfxZr1−xO2 Bilayer Stacks with Enhanced Endurance

Abstract: Hafnium zirconate (HZO) is investigated in metal-ferroelectric-metal capacitors as a function of Hf/(Hfþ Zr) atomic ratio, the presence of a thin ZrO 2 seed layer, and/or by doping HZO with La 3þ . It is demonstrated that a longer endurance is achieved with Hf-rich HZO by introducing a ZrO 2 seed layer. The endurance is further improved by introducing La 3þ in the Hf-rich HZO layer of the bilayer stack, which offers a higher 2P r in the pristine state compared with a stoichiometric HZO doped with the same amou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…Next, X-ray diffraction analysis was performed for the samples annealed by UV-LED at 450℃ for 15 s. First, we measured the grazing incidence x-ray diffraction (GIXRD) pattern and performed Rietveld refinement, which can be utilized to analyze the composition of the m-, o-, and t-phases in the HZO thin film [27][28][29][30][31].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Next, X-ray diffraction analysis was performed for the samples annealed by UV-LED at 450℃ for 15 s. First, we measured the grazing incidence x-ray diffraction (GIXRD) pattern and performed Rietveld refinement, which can be utilized to analyze the composition of the m-, o-, and t-phases in the HZO thin film [27][28][29][30][31].…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, UV-LED annealing is preferable for energy-and time-efficient annealing process to HL annealing. Also, it was indicated that the energy consumption was not largely affected by the maximum input power because the ramp-up time was roughly in inverse proportion to the maximum input power.Next, X-ray diffraction analysis was performed for the samples annealed by UV-LED at 450℃ for 15 s. First, we measured the grazing incidence x-ray diffraction (GIXRD) pattern and performed Rietveld refinement, which can be utilized to analyze the composition of the m-, o-, and t-phases in the HZO thin film[27][28][29][30][31].Fig.12shows the measured GIXRD pattern and the fitting curve obtained by Rietveld refinement. The incidence angle was fixed at 0.5°, and 2θ was ranged between 15 and 90° with 0.05° step.…”
mentioning
confidence: 99%
“…HZO is being explored for both FEFET [6]- [8] and FERAM [4], [9], [10] applications. Ferroelectricity in HZO has been demonstrated with Si [11], Al [11] as well as La [12]- [14]dopants. In undoped form, the coercive field of HZO layers is within ~0.9-1.2MV/cm range, which drops with addition of dopants in the layers to 0.5-0.7MV/cm [12].…”
Section: Introductionmentioning
confidence: 99%
“…Ensuring the reliability of device operation necessitates achieving a sufficiently high endurance device cycle with enough ferroelectric response . Although pure HZO exhibits a satisfactory ferroelectric response, it faces issues such as early breakdown and fatigue. , These challenges stem from the intrinsic vulnerability of HZO to reduction, potential generation of oxygen vacancies (V o ), and monoclinic phase evolution. , Therefore, pure HZO has been considered to be inappropriate for actual device applications.…”
Section: Introductionmentioning
confidence: 99%
“…To address these application issues, various dopants have been explored for the HZO layer. Among them, trivalent lanthanum (La 3+ ) has shown promising characteristics in terms of endurance and polarization. , La-doped HZO (La:HZO) generally showed lower initial two remanent polarization (2P r ) values and a larger wake-up effect, , likely caused by tetragonal phase stabilization in the presence of La dopant. Nevertheless, a delicate control of La dopant concentration allowed one to achieve a higher endurance cycle for device operation and maximum 2P r . , The La acceptor doping effect could mitigate the n-type nature of HZO, lowering the Fermi level, which decreased the leakage current and improved the endurance properties.…”
Section: Introductionmentioning
confidence: 99%